The impact of antibiotic use on clinical features and survival outcomes of cancer patients treated with immune checkpoint inhibitors - Zhou, Jiaxin; Huang, Guowei; Wong, Wan-Ching; Hu, Da-hai; Zhu, Jie-wen; Li, Ruiman; Zhou, Hong (Frontiers in Immunology, 2022)
Background: Nowadays, immune checkpoint inhibitors (ICIs) has become one of the essential immunotherapies for cancer patients. However, the impact of antibiotic (ATB) use on cancer patients treated with ICIs still remains controversial. Methods: Our research included the retrospective researches and randomized clinical trial (RCT), with cancer patients treated in ICIs and ATB, from public database of PubMed, web of science, EMBASE, Cochrane, clinical trials and JAMA. The survival outcomes included progression-free survival (PFS) and overall survival (OS). Meanwhile, Hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated, and subgroup analyses were performed to learn the concrete association between ATB use and the prognosis of cancer patients treated in ICIs. Results: Our results revealed that ATB use was associated with poor survival outcomes including OS (HR: 1.94, 95% CI: 1.68–2.25, p < 0.001) and PFS (HR: 1.83, 95% CI: 1.53–2.19, p < 0.001). The subgroup analysis learned about the association between ATB use and prognosis of cancer patients with ICIs treatment, including 5 cancer types, 3 kinds of ICIs types, 5 different ATP window, broad ATB class and ECOG score. ATB treatment was associated with poor OS of non-small-cell lung cancer (NSCLC), renal cell carcinoma (RCC), esophagus cancer (EC) and melanoma (MEL) in patients treated in ICIs, while non-small-cell lung cancer (NSCLC), renal cell carcinoma (RCC) were associated with poor PFS. Meanwhile, it was strongly related to ICIs type and ATB window. Furthermore, it is firstly mentioned that the use of broad ATB class was strongly associated with poor PFS. Conclusion: In summary, our meta-analysis indicated that the ATB use was significantly associated with poor OS and PFS of cancer patients treated in ICIs immunotherapy, especially for patients with ATB use in the period of (-60 days; +30 days) near the initiation of ICIs treatment. Also, different cancer types and the ICIs type can also impact the survival outcome. And it is firstly revealed the strong relationship between broad ATB class and worse PFS. Still, more research are needed for further study.